2022
DOI: 10.1093/nar/gkac407
|View full text |Cite
|
Sign up to set email alerts
|

Catchet-MS identifies IKZF1-targeting thalidomide analogues as novel HIV-1 latency reversal agents

Abstract: A major pharmacological strategy toward HIV cure aims to reverse latency in infected cells as a first step leading to their elimination. While the unbiased identification of molecular targets physically associated with the latent HIV-1 provirus would be highly valuable to unravel the molecular determinants of HIV-1 transcriptional repression and latency reversal, due to technical limitations, this has been challenging. Here we use a dCas9 targeted chromatin and histone enrichment strategy coupled to mass spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 100 publications
2
12
0
Order By: Relevance
“…Among those, we found that 10% of the proteins identified in our haploid screen are involved in host cell RNA processing and metabolism, such as DDX46 (also known as PRP5), involved in spliceosome assembly and RNA-protein interactions ( Cordin and Beggs, 2013 ) or EIF2B5, involved in translation initiation ( König et al., 2008 ). In another study, we performed locus-specific chromatin pulldown of the HIV-1 5´LTR latent versus active promoter coupled with mass spectrometry in order to identify differentially abundant putative repressors or activators of latency (in press ( Ne et al., 2022 )). We found that 50% of the putative repressor proteins bound to the latent promoter were proteins involved in RNA processing and metabolism, including members of the TREX1 and TREX2 complexes (DDX39A and PCID2) ( Heath et al., 2016 ; Stewart, 2019 ), and RAMAC/FAM103A1, required for mRNA cap methylation ( Gonatopoulos-Pournatzis et al., 2011 ).…”
Section: What’s Rna Got To Do With It? the Contribution Of Rna-bindin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, we found that 10% of the proteins identified in our haploid screen are involved in host cell RNA processing and metabolism, such as DDX46 (also known as PRP5), involved in spliceosome assembly and RNA-protein interactions ( Cordin and Beggs, 2013 ) or EIF2B5, involved in translation initiation ( König et al., 2008 ). In another study, we performed locus-specific chromatin pulldown of the HIV-1 5´LTR latent versus active promoter coupled with mass spectrometry in order to identify differentially abundant putative repressors or activators of latency (in press ( Ne et al., 2022 )). We found that 50% of the putative repressor proteins bound to the latent promoter were proteins involved in RNA processing and metabolism, including members of the TREX1 and TREX2 complexes (DDX39A and PCID2) ( Heath et al., 2016 ; Stewart, 2019 ), and RAMAC/FAM103A1, required for mRNA cap methylation ( Gonatopoulos-Pournatzis et al., 2011 ).…”
Section: What’s Rna Got To Do With It? the Contribution Of Rna-bindin...mentioning
confidence: 99%
“…( Figure 2B ). Spliceosome protein CRNKL1 has been recently implicated in promoting nuclear retention of intron-containing US vRNA species and its depletion leads to improved export of US vRNA ( Figure 2B ) ( Xiao et al., 2021 ; Ne et al., 2022 ). On the contrary, other proteins can act as positive regulators of US vRNA export and their absence leads to nuclear retention of such species.…”
Section: Co and Post-transcriptional Regulation Of Hiv-1 Gene Express...mentioning
confidence: 99%
“…Strategies that use combinatorial approaches of LRAs could result in higher efficacy in reactivating HIV-1 latency (5). We have shown in previous studies that the effect of pyrimethamine on HIV-1 latency ex vivo could be potentiated when combined with other LRAs including HDACi (44,46). We therefore designed the study to include a combinatorial arm to test whether the effect of the individual LRAs could be potentiated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our preclinical studies identified BRG-Brahma associated factor (BAF) complex inhibitors (BAFi) as a novel LRA class, which we demonstrated enhanced the activity of other LRA classes (44)(45)(46). The BAF (mammalian SWI/SNF) chromatin remodeling complex is a key repressor of HIV-1 latency that uses adenosine triphosphate (ATP) hydrolysis to position repressive nucleosome nuc-1 at the HIV-1 long-terminal repeat, causing transcriptional silencing of HIV-1 gene expression, thereby maintaining HIV-1 latency (47,48).…”
Section: Introductionmentioning
confidence: 96%
“…The contribution of these RNA processing mechanisms to the overall repression of HIV-1 gene expression has recently been characterized in both in vitro models of HIV-1 latency and CD4+ T cells obtained from people living with HIV-1 (PLWH) 1014 , where it has been shown that blocks to HIV-1 gene expression occur largely at post-transcriptional levels. More recently, several unbiased and candidate studies, including our own, have successfully identified co– and post-transcriptional regulators of HIV-1 latency that control vRNA metabolism and either promote or inhibit viral gene expression 12,15,16 .…”
Section: Introductionmentioning
confidence: 99%